Linear-Rational Term Structure Models With Flexible Level-Dependent Volatility - Schwellnus, Adrian (African Institute of Financial Markets and Risk Management, 2019)
The Linear-Rational Framework for the modelling of interest rates is a framework which allows for the addition of spanned and unspanned factors, while maintaining a lower bound on rates and tractable valuation of interest rate derivatives, particularly swaptions. The advantages of having all these properties are significant. This dissertation presents the Linear-Rational Framework, and specializes the factor process to a class of diffusion models which allows for the degree of state dependence of volatility to be estimated. This dissertation then finds that the estimated state dependent volatility structure is significantly different to that of typical models, where it is set it a priori. The effect the added degree of freedom has on the model implied swaption skew is then analysed.